Prognostic implications of left ventricular diastolic dysfunction in moderate aortic stenosis. (4th February 2022) - Stassen, J; Ewe, SH; Butcher, SC; Ammanullah, MR; Hirasawa, K; Singh, GK; Ding, ZP; Pio, SM; Chew, NWS; Sia, CH; Kong, WKF; Poh, KK; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): ESC Training Grant App000064741 Background Moderate aortic stenosis (MAS) is associated with an increased risk of adverse events. Although left ventricular (LV) diastolic dysfunction (DDF) has shown to carry an unfavorable prognosis in severe AS, the prognostic value of LV DDF in MAS has not been investigated. Purpose To investigate the prognostic impact of LV DDF in patients with MAS and preserved LV ejection fraction (EF). Methods LV diastolic function was evaluated in patients with MAS (aortic valve area >1.0 and ≤1.5cm2)  and preserved LVEF (≥50%) using echocardiography according to the 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging guidelines. Clinical outcomes were defined as all-cause mortality and a composite endpoint of all-cause mortality and aortic valve replacement (AVR). Results Of 1247 patients (age 74 ± 10 years, 47% men) with MAS and preserved LVEF, 396 (32%) had normal diastolic function, 316 (25%) had indeterminate diastolic function and 535 (43%) had DDF. Patients with DDF were more likely to be female, had more comorbidities (hypertension, atrial fibrillation, chronic kidney disease) and were more symptomatic (NYHA ≥2) than patients with normal diastolic function. Patients with DDF also had smaller aortic valve area and higher peak aortic velocities than patients with normal/indeterminate diastolic function. During a median follow-up of 53 (26 – 81) months, 484 (39%) patients died. For the composite endpoint, 770 patients (62%) underwent AVR (n = 376) or died (n = 394) during a median follow-up of 37 (IQR 15 – 62) months. Patients with DDF had significantly lower survival rates (p <0.001) and event-free survival rates (p = 0.015) compared to patients with normal/indeterminate diastolic function (Figure 1). On multivariable analysis, DDF was independently associated with all-cause mortality (HR: 1.368; 95% CI: 1.085 – 1.725; p = 0.008) and the composite endpoint of all-cause mortality and AVR (HR: 1.241; 95% CI: 1.035 – 1.488; p = 0.020) (Figure 2). Conclusion: LV DDF is associated with worse outcomes in patients with MAS. Assessment of LV diastolic function may contribute significantly to risk stratification of patients with MAS.